2012
DOI: 10.1039/c2cc34026g
|View full text |Cite
|
Sign up to set email alerts
|

Coarctate cyclization reactions: a primer

Abstract: The cleavage of five-membered heterocycles possessing an exocyclic carbene or nitrene to form conjugated ene-ene-yne systems has been documented for over 40 years; however, the reverse reaction, using a conjugated ''ene-ene-yne'' precursor to form a heterocycle is a relatively new approach. Over the past decade, the Haley and Herges groups have studied computationally and experimentally the cyclization of the ''hetero-ene-ene-yne'' motif via an unusual class of concerted reactions known as coarctate reactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Our calculations [B3LYP/6-311G(2d,2p)] reveal that the relative energy of the resulting singlet carbenes, relative to their parent diazirines, increases following the order 6b Ͻ 24b Ͻ 14b. [25] Sheridan et al proposed similar open-chain products formed from 2-diazirinylbenzothiophenes. The rise in entropy by converting one molecule into two will result in a clearly negative free reaction enthalpy.…”
Section: Dft Calculationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our calculations [B3LYP/6-311G(2d,2p)] reveal that the relative energy of the resulting singlet carbenes, relative to their parent diazirines, increases following the order 6b Ͻ 24b Ͻ 14b. [25] Sheridan et al proposed similar open-chain products formed from 2-diazirinylbenzothiophenes. The rise in entropy by converting one molecule into two will result in a clearly negative free reaction enthalpy.…”
Section: Dft Calculationsmentioning
confidence: 97%
“…That type of reaction is known to proceed through low barriers (3-5 kcal/mol). [25] Sheridan et al proposed similar open-chain products formed from 2-diazirinylbenzothiophenes. [12] According to our calculations, only the reaction of carbene 24b to transoid diimine 24c is exothermic (-4.5 kcal/mol).…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Herges, Young and Haley have investigated the cyclization of aryltriazenes at 170-200 o C, where formation of cinnolines 180 is a pericyclic reaction via an azimine 179, whereas the alternative formation of 2H-indazole derivatives 182 is ascribed to a coarctate reaction via the carbene 181 (Scheme 51) [166,167]. The two reaction pathways have almost the same calculated activation barriers, 30-31 kcal/mol, but by replacing the acetylenic H by COOMe, the coarctate path becomes distinctly preferred by ca.…”
Section: Triazane and Triazenesmentioning
confidence: 99%
“…This proved to be exactly the case in 2000 when graduate student Dave Kimball serendipitously found that we could prepare five-membered and six-membered heterocycles from the azo-ene-yne precursors used to synthesize the annulenes. [5] If I had known what Dave was doing, I would have told him, "don't waste your time". Instead, that screw-up led to 21 published papers.…”
mentioning
confidence: 99%